Identifikasi Genetik Ikan Teri dari Teluk Cenderawasih dengan pendekatan DNA Barcoding - Muhammad Dailami; Yuni Widyawati; Abdul Hamid A. Toha (Faculty of Agriculture Musamus University, 2021)
The Cenderawasih Bay is a marine habitat for whale sharks (R. typus) which appear almost all year round. The appearance of this whale shark is triggered by various factors, including the food. Anchovy is one of the attractions for the emergence of whale sharks, so it is necessary to conduct genetic, biological and ecological studies. Anchovy has a small in size, making it difficult to identify morphologically. The purpose of this study was to genetically identify anchovy samples obtained from Cenderawasih Bay and compare the sequences with the GenBank database. The COI gene fragments were amplified by PCR method, using primer jg-LCO and jg-HCO. Sequencing is carried out from two directions, forward and reverse with the sanger termination dideoxy method. The resulting DNA sequence has a length of 669 base pairs encoding 223 amino acids. The results of homological comparisons with the NCBI and BOLD System databases show that this sample has similarities to the COI sequence of Spratelloides gracilis with a similarity number up to 99%. The results of the phylogenetic tree analysis showed that the anchovy samples from Cenderawasih Bay were in one clade with S. gracilis from Japan and separated from the clade of S. gracilis from the Red Sea, with a distance between clades is 0.104. This result is in line with the identification by homological comparison in the NCBI and BOLD System.